Effect of nephroprotective Ficus dalhousiae bark extract on gentamicin induced with combination of benzoic acid nephrotoxicity in rats - Jahan, Roshan; Singh, Sangeeta (International Journal of Basic & Clinical Pharmacology, 2021)
Background: The Ficus dalhousiae plant (Anjeer family) is. Its important parts-leaves, stem, bark and root are. The current study is design to effect of Ficus dalhousiae bark extract on gentamicin (GM) induced with combination of benzoic acid (BA) nephrotoxicity in rats. Methods: In acute toxicity studies animals are fasted before being dosed; kept overnight. Depending on the time interval. The beginning dose will be chosen from one of four predetermined levels: 5, 50, 300, or 2000 mg/kg of body weight. The animals are evaluated for 4 and 48 hours. In nephroprotective studies we are taken 30 rats which will be divided into 5 groups. proceed group by group like-control with normal saline, BA (100 mg/kg/body weight, IP) daily, hydroalcoholic extract of Ficus dalhousiae (200 mg/kg/body weight, PO) and simultaneously administered GM (100 mg/kg/body weight, IP) daily for 9 days. And we are doing difference types of estimations, like-blood urea, uric acid and serum creatinine. Results: Ficus dalhousiae bark extract on BA action on serum creatinine and urea levels in rats given GM. When compared to control rats, eight days of GM treatment resulted in significantly higher serum creatinine and urea levels. However, BA pretreatments have significantly improved serum creatine and urea (p<0.001) to reduce GM-induced nephrotoxicity (p<0.01, resp.). Conclusions: Ficus dalhousiae has significant nephroprotective activity in nephroprotective studies, acute toxicity activity and various such type of estimations like- blood urea, uric acid and creatinine.